Men of color : a context for service to homosexually active men - Longres, John F. (New York London : Harrington Park Press, 1996)
Fonds Suzan Daniel (FSD)ook uitgegeven als Journal of Gay & Lesbian Social Services 05(1996) 2-3
Ook verschenen in: Journal of gay and lesbian social services, vol. 5, no. 2/3 1996, James J. Kelly, editor
Engels
Monografie